2020
DOI: 10.1101/2020.05.28.121269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery of Consciousness and Cognition after General Anesthesia in Humans

Abstract: Understanding how consciousness and cognitive function return after a major perturbation is important clinically and neurobiologically. To address this question, we conducted a three-center study of 30 healthy humans receiving general anesthesia at clinically relevant doses for three hours. We administered a pre-and post-anesthetic battery of neurocognitive tests, recorded continuous electroencephalography to assess cortical dynamics, and monitored sleep-wake activity before and following anesthetic exposure. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(54 reference statements)
2
1
0
Order By: Relevance
“…In this study with healthy adults exposed to a clinically relevant anesthesia regimen, we demonstrated that six distinct cognitive functions follow different temporal trajectories of recovery following anesthesia, with certain cognitive functions returning to baseline only 90-180 min following the recovery of consciousness. These results were supported by a larger study of 60 individuals (including those in this study) showing that the rates of recovery statistically differed among cognitive domains upon recovery from anesthetic-induced unconsciousness (Mashour et al, 2020). Importantly, we found that brain networks associated with cognitive tasks are significantly altered after a period of profound anesthesia-induced unconsciousness, return to their baseline state 30-60 min following recovery of consciousness, and are distinct and dissociable across various cognitive functions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study with healthy adults exposed to a clinically relevant anesthesia regimen, we demonstrated that six distinct cognitive functions follow different temporal trajectories of recovery following anesthesia, with certain cognitive functions returning to baseline only 90-180 min following the recovery of consciousness. These results were supported by a larger study of 60 individuals (including those in this study) showing that the rates of recovery statistically differed among cognitive domains upon recovery from anesthetic-induced unconsciousness (Mashour et al, 2020). Importantly, we found that brain networks associated with cognitive tasks are significantly altered after a period of profound anesthesia-induced unconsciousness, return to their baseline state 30-60 min following recovery of consciousness, and are distinct and dissociable across various cognitive functions.…”
Section: Discussionsupporting
confidence: 88%
“…In the control group, a significant difference in performance scores was only found for the VOLT test at session eight compared to session one (Supplementary Figure 1), demonstrating that the changes observed in the experimental group were a direct result of anesthesia-induced unconsciousness, and not related to fatigue or learning effects. These results parallel the cognitive recovery trajectories of participants in the full ReCCognition study, wherein 30 individuals showed differential recovery times following anesthesia of the speed and accuracy of tasks associated with attention, complex scanning and visual tracking, working memory, and executive function (Mashour et al, 2020).…”
Section: Temporal Recovery Of Cognitive Performance Varies By Task After Anesthesia-induced Unconsciousnesssupporting
confidence: 65%
“…Propofol suppresses neuronal activity mainly through an enhancement of GABA-A receptor-mediated inhibition thus modulating widespread targets throughout the brain ( Alkire et al, 2008 ). In terms of safety in healthy volunteers, a multicenter, 30-participant study demonstrated no adverse effects of surgical anesthesia (in the absence of surgery), with cognition returning to baseline 3-hours after emergence from a prolonged anesthetic, without signs of disrupted arousal states in the following days, suggesting the healthy human brain is resilient even to deep anesthesia ( Mashour et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%